STRATEGIES AND TECHNIQUES OF TRANSLATION IN TRANSLATING SONGS AS 21ST CENTURY CURRICULUM - ANWAR, FARRAH ZAKIYAH (Manajemen Pendidikan, 2020)
Song is one of English material in 21st century curriculum at senior high school. To produce memorable and beautiful meaning, song lyrics comprise language variation, figurative language, idioms, and pragmatics. However, students will face problems in translating and comprehending the meaning of the song lyric. Therefore, to figure out the message and the intended meaning from the song lyrics, the students should understand techniques and strategies in translation. Regarding with the statements, the aims of this study are to find out kinds of difficulty faced by the students, to analyze kinds of translation technique used by the students and strategies to overcome their difficulties in translating English song.  In conducting the research, the writer used descriptive qualitative research based on Creswell theory. The result of the research showed that the students faced difficulties in determining figurative language, idiom, linguistics factors grammatical, referential, connotative, and contextual meaning in song lyric. There are six translation techniques used by the students: literal translation, reduction, modulation, amplification, linguistic compression, and transposition. There are several strategies can be used to help students in translating variation of meaning in English song: shifting shape, shape in meaning, adaptation, contextual matching and matching recorded. Learning techniques of translation and their strategies are useful for receiving better understanding in language enhancement. In addition, to translate the source into target language, students will also have a good comprehension of the song?s content.